2019
DOI: 10.21273/hortsci14066-19
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Accumulation and Root Distribution of Grafted Tomato Plants as Affected by Nitrogen Fertilization

Abstract: Growth and yield typically increase when tomato plants are grafted to selected interspecific hybrid rootstocks from which distinctive root system morphologies are envisioned to aid nutrient uptake. We assessed these relationships using a range of exogenous nitrogen (N) supplies under field production conditions. This study analyzed the impact of N on growth, root distribution, N uptake, and N use of determinate ‘Florida 47’ tomato plants grafted onto vigorous, interspecific, hybrid tomato rootstocks ‘M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
2
8
1
1
Order By: Relevance
“…Thus, differences in root system traits may not have played a critical role in plant growth. Our finding also differs from grafting studies in tomato ( Djidonou et al, 2019 ) and cucurbits ( Nawaz et al, 2017 ; Liang et al, 2021 ) that have found increased plant vigor and yield due to the enhanced nutrient uptake and supply by the rootstock. While basil growth seems relatively unaffected by nutrient supply, studies have shown nutrient supply to alter the concentrations of commercially important compounds in basil ( Zheljazkov et al, 2008 ; Ciriello et al, 2020 ; Kolega et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, differences in root system traits may not have played a critical role in plant growth. Our finding also differs from grafting studies in tomato ( Djidonou et al, 2019 ) and cucurbits ( Nawaz et al, 2017 ; Liang et al, 2021 ) that have found increased plant vigor and yield due to the enhanced nutrient uptake and supply by the rootstock. While basil growth seems relatively unaffected by nutrient supply, studies have shown nutrient supply to alter the concentrations of commercially important compounds in basil ( Zheljazkov et al, 2008 ; Ciriello et al, 2020 ; Kolega et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 99%
“…With regards to the effects of rootstock genotypes on shoot N concentration, contradictory results have been reported for interspecific rootstocks of S. lycopesicum × S. habrochaites. Most of the reports conclude that genotypes such as Beaufort, Mutifort or He-Man increase the concentration of N in the shoot [34][35][36]. Another common rootstock is Maxifort which has shown genotype-specific responses to shoot N concentration.…”
Section: Nitrate Content In the Xylem Sapmentioning
confidence: 99%
“…Money Maker as scion, it does not affect shoot N concentration [36], while the effect on cv. Primadonna as scion was to promote N content in the shoot biomass, in comparison to non-grafted plants [35].…”
Section: Nitrate Content In the Xylem Sapmentioning
confidence: 99%
“…Kelimpahan unsur C dan N yang tinggi pada tomat sambung sejalan dengan temuan Li et al (2014) dan Nie et al, (2010), bahwa tomat sambung memiliki konsentrasi CO2 pada akar tanaman dan sumber N di eksudat akar yang lebih tinggi dibandingkan dengan tanaman tanpa sambung. Djidonou et al (2019) juga melaporkan bahwa tomat sambung mampu mengurangi hilangnya pencucian unsur N dengan penyerapan N yang tinggi di akar.…”
Section: Hasil Dan Pembahasan Intensitas Penyakit Layu Bakteriunclassified